Kaji Eksperimental Pengaruh Pembebanan terhadap Emisi Debu Partikulat pada Motor Bensin - Khairil, Khiaril; Hamdani, Hamdani; Jalaluddin, Jalaluddin (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2011)
The effect of engine loading on emission of particulate matter was studied by using an Otto engine (Honda astrea grand 110 cc). In the experiment, the characteristics of loading engine, fuel consumption and composition of particulate matter were investigated. The engine loading was determinated in term of engine transmittion, the fuel consumption was measured by using plastic tube scale, and composition of deposit particulate matter was analyzed by using spectrophotometer. The experimental results show that the quantity and fuel consumption was increased by the increasing engine loading. The deposite of particulate matter was generally characterized by organic carbon content.Keyword: motor bensin, emisi debu, transmisi